Barriers to green innovation initiatives among manufacturers: the Malaysian case - Abdullah, M.; Zailani, S.; Iranmanesh, M.; Jayaraman, K. (Springer Verlag (Germany), 2016)
This study investigated the internal and external barriers to green innovation initiatives among Malaysian manufacturers. Data was gathered through a survey of 153 manufacturing companies in Malaysia. Data was analyzed using the partial least squares technique. Results indicated that the barriers to green products, processes, and systems innovations are different. Issues of environmental resources, attitude and perception, business practices, government support, and customer demand were found to be the barriers to green product innovations, whereas attitude and perception, business practices, poor external partnerships, insufficient information, lack of customer demand, and environmental commercial benefits were determined to be the factors that negatively affect green process innovations. As regards green system innovation, environmental resources, attitude and perception, business practices, technical barriers, government support, and environmental and commercial benefits presented themselves as the internal and external barriers that need to be addressed. The results have important implications for managers of manufacturers that have plans of promoting green products, processes, and system innovations.